Identification and Evaluation of Apoptosis-Inducing Activity of Ipomone from Ipomoea nil: A Novel, Unusual Bicyclo-[3.2.1] Octanone Containing Gibberic Acid Diterpenoid - Goel B.; Chatterjee E.; Dey B.; Tripathi N.; Bhardwaj N.; Khattri A.; Guru S.K.; Jain S.K. (My University, 2025)
Ipomone (1), a novel diterpenoid along with seven known compounds (2-8), was isolated for the first time from the acidified hydroalcoholic extract of Ipomoea nil seeds. The structures of the isolated compounds were elucidated via comprehensive NMR spectroscopic data. The absolute configuration of 1 was ascertained through NOESY, NMR, and ECD analyses. Compound 1 was found to contain an unusual bicyclo-[3.2.1] octanone, which appeared first time in any natural product that might be an artifact resulting from the acid-catalyzed 1,2 alkyl shift/rearrangement. The novel compound was screened for cytotoxic activity against a panel of 12 human cancer cell lines and exhibited weak cytotoxicity with IC50 values in the range of 34-86 μM (except for HEK-293 cells). Microscopic studies revealed that compound 1 induced apoptosis and autophagy in A549 cells. To further explore the signaling pathway involved, immunoblot analysis was performed that confirmed inhibition of apoptotic proteins PARP-1 and caspase-3 expression and upregulation of LC3B expression by compound 1. The compound was further subjected to molecular docking studies to evaluate its binding affinity with p110α, PARP-1, and caspase-3 proteins. © 2021 The Authors. Published by American Chemical Society.